Dakwah di Media Siber - Aan Herdiana (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
The Internet gives a new universal space for sharing information, and interacting. The use of the Internet network, in the context of da’wah is a breakthrough for the efficiency and effectiveness of da’wah. The birth of Islamic sites is a must for today’s adult da’wah activists. However, da’wah should evolve and adapt to the ever-changing character of society, so da’wah can be well received. One of the sites containing Islamic values is juguransyafaat.com. The method used in this study is semiotics, where this theory is used to interpret the meaning of the text, whether in the form of words or images. The result of this research explains that through the writings or articles it is seen that the discourse presented in juguransyafaat.com gives the characteristics of the propagation material, which when classified into three major parts, which in cludes aqidah, life, and morals to create innovative thinking which is expected to change the establishment of the understanding of religion from a closed understanding to an open religious understanding.